Los extractos de Ovidio en las Sententiae et Exempla (1557) de André Rodrigues de Évora: Fastos, Tristes y Pónticas - Rodríguez Herrera, Gregorio (Coimbra: Universidade de Coimbra, 2020)
En este trabajo analizamos la selección de Fastos, Tristes y Pónticas de Ovidio presentes en las Sententiae et Exempla (Lyon 1557) de André Rodrigues, para concluir a) que los extractos, en línea con la tradición medieval, son sentencias de carácter general sobre vicios, virtudes o paradigmas de comportamiento en las que Ovidio se presenta como auctoritas; b) que las Sententiae veterum poetarum de G. Maior son el principal hipotexto de André Rodrigues; y c) que el De poetica virtute de A. Mancinelli también estuvo en la génesis del florilegio del Eborense.
This paper addresses the selection of passages from Fasti, Tristia and Epistulae ex Ponto used in the Sententiae et Exempla (Lyon 1557) by André Rodrigues. From our analysis we can draw the following conclusions: (a) these passages, in line with the medieval tradition, are general sentences on vices, virtues or patterns of behaviour in which Ovid embodies the auctoritas; (b) the Sententiae veterum poetarum by G. Maior are André Rodrigues’s main hypotext; and, (c) De poetica virtute by A. Mancinelli was also involved in the genesis of the florilegium of the author from Évora.
Keywords: Ovidio Nasón, Publio; Rodrigues de Évora, André -- 1557